Strategi Pelestarian Tari Topeng Kelana di Era Modern pada Sanggar Nimas Mayangsari - Tania Puji Lestari; Naila Farah (Nazharat: Jurnal Kebudayaan, 2026)
This study discusses the preservation strategy of the Kelana Mask Dance in the modern era at the Nimas Mayangsari Studio, Cirebon Regency. This research is important because the development of modern entertainment and changes in people's interests pose challenges to the sustainability of traditional arts. The purpose of this study is to determine the strategy used by the Nimas Mayangsari Studio in preserving the Kelana Mask Dance amidst the changing times. The approach used is qualitative with descriptive methods. Data were obtained through observation, interviews, and documentation with informants. Data analysis was carried out using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results show that the preservation strategy is carried out through coaching the younger generation in dance training, introducing philosophical values, utilizing social media, and collaborating with educational institutions. This strategy shows that the preservation of traditional arts requires the ability to adapt to social and technological developments without eliminating the cultural values ​​that are the identity of the region.